The impact of digital trade development on China's export of technology-intensive products: Evidence from importing countries. - Chenggang Wang; Fan Meng; Tiansen Liu (PLoS ONE)
Developing exports of technology-intensive products is a key focus for China's high-quality foreign trade development. The rapid growth of global digital trade brings new opportunities and challenges for China's exports of technology-intensive products. This paper utilizes panel data from 2005 to 2022. And we construct an extended gravity model to thoroughly investigate the impact of digital trade development in importing countries on China's exports of technology-intensive products. The research findings indicate: (1) The development of digital trade in importing countries significantly promotes China's exports of technology-intensive products. This effect is more pronounced beyond a certain threshold. (2) The reduction of trade costs and increased foreign direct investment play intermediary roles in facilitating the impact of digital trade in importing countries on China's exports of technology-intensive products. However, institutional distance exerts a negative inhibitory effect on this process. (3) The impact of digital trade development in importing countries on China's exports of technology products varies due to differences in product types, national income levels, regional characteristics, economic cooperation, and market potential. The conclusions of this paper provide theoretical and empirical evidence for the Chinese government to enhance the efficiency of exporting technology-intensive products.